Students' inclinations towards games and perceptions of Game-Based Learning (GBL) - Ariffin, M.M. (Institute of Electrical and Electronics Engineers Inc., 2014)
The term 'games' has remained as one of the most popular search terms in Google for the past 10 years. Looking at games' popularity, especially among the youth, there is a need for academicians and educationists to find ways in which games might support learning. In order to ensure a close match between the learning activities and the expected outcome, instructors should aware of the learners' needs and their perception towards Game-Based Learning (GBL). The research focuses on the learner specification dimension in the Four-Dimensional Framework (FDF). The method of study was through a survey and the target audience is student of Universiti Teknologi Petronas. The research adopted convenience sampling and 208 samples were collected. The outcomes of this paper are twofold: first is the identification of sets of game characteristics to be used either by game developers or instructors, and second is an indication of the viability of games as an educational tool for Higher Education settings. Â© 2014 IEEE.